2015
DOI: 10.1021/acs.joc.5b00678
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Course of Wittig Rearrangements of Dihydropyran Allyl Propargyl Ethers

Abstract: 2,3]-Wittig rearrangements of sugar-derived dihydropyran allyl propargyl ethers located at the 2-or 4-position have been studied as useful means for extending the carbon chains of the 4-or 2-position with chirality transfer. The stereochemical course of these reactions depends on the following factors: (1) deprotonation of pro-R or pro-S-H, (2) equilibration of the lithiated stereogenic carbanion, (3) conformational inversion during the rearrangement, and (4) concerted [2,3]-or [1,2]-Wittig rearrangement. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, the application of WR on pyranosederived allyl propargyl ethers was reported. 13 We have been exploring the synthesis of various bioactive/ important carbon-branched sugars 14−17 involving Claisen rearrangement. 18 In connection to that, we were prompted to investigate the WR on a carbohydrate scaffold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the application of WR on pyranosederived allyl propargyl ethers was reported. 13 We have been exploring the synthesis of various bioactive/ important carbon-branched sugars 14−17 involving Claisen rearrangement. 18 In connection to that, we were prompted to investigate the WR on a carbohydrate scaffold.…”
mentioning
confidence: 99%
“…In this connection, the [1,2]- or [2,3]- WR of carbohydrate acetals has been studied to convert the O -glycosides into C -glycosides. Recently, the application of WR on pyranose-derived allyl propargyl ethers was reported …”
mentioning
confidence: 99%
“…Nevertheless, methods based on the use of (i) strong Brønsted bases, such as n -BuLi or t -BuLi, in the presence of a stoichiometric ligand, and (ii) stoichiometric amounts of a chiral boron reagent have been reported . Moreover, stereoselective [2,3]-rearrangements with substrates bearing either existing stereocenters , or chiral auxiliaries , (Scheme a) to control the configuration of the newly formed σ-bond have been studied. Although rare, more recently, different groups have described interesting organocatalyzed asymmetric [2,3]-rearrangement methodologies of allyloxy derivatives for the asymmetric synthesis of allylic alcohols.…”
mentioning
confidence: 99%
“…By forming homoaggregated organolithium species, LiCl has similar properties, and actually its addition leads to spectacular yield and stereoselectivity improvements (85%, 93/7: syn / anti , entry 7) even reproducible on a 3 g scale. It has been reported that LiBr suppressed concurrent [1,2]-Wittig rearrangement, but the effect of Li + on syn / anti selectivity has not been reported before. The use of MeLi·LiBr (entry 10) still led to a good yield, but with a lower selectivity.…”
mentioning
confidence: 99%